Fostering Diversity: The Crucial Role of Organizations - Kumar, Rupesh (Journal of Advanced Research in HR and Organizational Management, 2023)
This article explores the significance of diversity, emphasizing its role in organizational development through a case study. The authors advocate for policies that promote diversity in various facets of organizations, stressing its positive impact on innovation, tolerance, and cultural heritage. This comprehensive article delves into the multifaceted aspects of diversity within organizations, emphasizing its profound impact on innovation, tolerance, and cultural richness. Through insightful discussions and a compelling case study, the authors illuminate the need for robust policies that champion diversity at every organizational level. By scrutinizing the PROGRESS framework and categorizing diversity into primary and secondary dimensions, the article provides a nuanced understanding of the various facets that contribute to a diverse environment. The significance of cross-cultural training is underscored as a transformative tool for fostering sensitivity and appreciation among individuals from different backgrounds.